Biodegradation of petroleum sludge by methylobacterium sp. strain ZASH - Shamsul Harumain, Zakuan Azizi; Mohamad, Mohd Azrul Naim; Nordin, Noor Faizul Hadry; Abd Shukor, Mohd Yunus (Penerbit Universiti Sains Malaysia, 2023)
A bacterium was isolated from sludge-contaminated soil in a petroleum refinery and tested for its ability to degrade aliphatic hydrocarbon compounds present in petroleum sludge. The isolate was grown on minimal salt media agar supplemented with 1% (w/v) petroleum sludge. The isolate was tentatively identified as Methylobacterium s p. s train ZASH based on the partial 16s rDNA molecular phylogeny. The bacterium grew optimally between the temperatures of 30°C and 35°C, pH 7 and 7.5, 0.5% and 1.5% (v/v) Tween 80 as the surfactant, and between 1% and 2% (w/v) peptone as the nitrogen source. The constants derived from the Haldane equation were ?max = 0.039 hr–1, Ks = 0.385% (w/v) total petroleum hydrocarbons (TPH) or 3,850 mg/L TPH, and Ki =1.12% (w/v) TPH or 11,200 mg/L. The maximum biodegradation rate exhibited by this strain was 19 mg/L/hr at an initial TPH concentration of 10,000 mg/L. Gas chromatography analysis revealed that after 15 days the strain was able to degrade all aliphatic n-alkanes investigated with different efficiencies. Shorter n-alkanes were generally degraded more rapidly than longer n-alkanes with 90% removal for C-12 compared to only 30% removal for C-36. The addition of sawdust did not improve bacterial degradation of petroleum hydrocarbons, but it assisted in the removal of remaining undegraded hydrocarbons through adsorption.